The Role of the Civil Sector in the Integration and Protection of Migrants’ Human Rights in Serbia: Normative Framework and Practical Experiences - Batrićević, Ana; Kubiček, Andrej (Zbornik Instituta za kriminološka i sociološka istraživanja, 2019)
The arrival of a large number of migrants that occurred in Serbia in the past couple of years has required a prompt and adequate reaction of both state bodies as well as the civil sector in order to facilitate the protection of their fundamental human rights and the respect of security. In spite of numerous international and national legal sources prescribing the state’s obligations in the area of migrants' human rights protection and the establishment of circumstances suitable for their integration, it seems that the response of official state bodies to the so-called migrant crises would not be as suitable and efficient as it is supposed to be without the parallel participation of the civil sector. Having that in mind, the authors of this paper intend to analyse current legal frameworks pertinent to the protection of migrants' human rights in Serbia, as well as to explore recent examples of good practice of non-governmental organisations directed towards the protection of migrants' human rights and assisting them on the path of their integration in our country.